Inventory of Fish Captured in the Komering River Sukadarma Village Jejawi District Ogan Komering Ilir Regency - Khusnul Khotimah; Togar Sakabani; Muhammad Nizar; Meika Puspita Sari; Helmizuryani Helmizuryani; Elva Dwi Harmilia (Universitas Muhammadiyah Palembang, 2026)
Information on fish species composition is essential for evaluating the ecological condition of river ecosystems and providing a scientific basis for sustainable fisheries management. However, data on fish diversity in the Komering River, particularly in Sukadarma Village, Jejawi District, Ogan Komering Ilir Regency, remain limited. Therefore, this study aimed to inventory fish species caught in the Komering River and assess their diversity, evenness, and dominance. The research was conducted from February to May 2024 at five observation stations using a purposive sampling approach. Fish sampling was carried out four times per month for three consecutive months. Data were analyzed using the Shannon–Wiener diversity index (H'), evenness index (E), and Simpson's dominance index (C). A total of 635 individual fish representing 21 species were recorded during the study. The diversity index ranged from 1.03 to 3.42, indicating moderate diversity at Stations 1–4 (H' = 1.03–2.78) and high diversity at Station 5 (H' = 3.42). Evenness values ranged from 0.51 to 0.98, indicating that fish individuals were generally distributed evenly among species. Dominance index values ranged from 0.18 to 0.62, with only Station 3 showing species dominance (C = 0.62), while the remaining stations exhibited no dominant species. These findings indicate that the Komering River in Sukadarma Village still supports relatively stable freshwater fish communities with moderate to high biodiversity, providing important baseline information for fisheries resource management and biodiversity conservation.